The effect of acupressure at spleen 6 acupuncture point on the anxiety level and sedative and analgesics consumption of women during labor: A randomized, single-blind clinical trial - Parisa Samadi; Zahra Alipour; Minoor Lamyian (Wolters Kluwer Medknow Publications, 2018)
Background: Labor pain is the most severe pain women would experience, which could lead to loss of emotional control that plays a key role in creating a traumatic delivery experience and psychological disorders. The goal of this study was to evaluate the effect of acupressure on anxiety level and sedative and analgesics consumption in women during labor. Materials and Methods: This study was a randomized, single-blind clinical trial performed at Maryam Hospital in Tehran, Iran. One hundred and thirty-one pregnant women in Labor Ward were selected by convenience sampling. Subjects were randomly allocated to three groups, namely experimental group (pressure group), control group 1(touh group) and, control group 2 (routine care group). The study data were gathered using demographic information form, and assessed with Faces Anxiety Scale (FAS). For participants belonging to the experimental group, pressure was applied to the Spleen 6 acupoint for 30 min, and for those with only light touch was applied to the Spleen 6 acupoint for 30 min. The collected data were analyzed using Statistical Package for the Social Sciences 16 and descriptive statistics. Results: There was a significant difference between the three groups in terms of the mean of anxiety after 30 min of starting the intervention and 30 min after termination of the intervention; the anxiety of the experimental group was significantly decreased (p = 0.03). Sedative and analgesics consumption was significantly lower in the experimental group compared to the other groups (p = 0.006). Conclusions: This study showed that compression of the Spleen 6 acupoint was an effective complementary method to decrease maternal anxiety and analgesic consumption, especially pethidine.